Windows 8 App Projects - XAML and C# Edition - Vermeir, Nico.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
Become a leading Windows 8 app developer by using Windows 8 App Projects - XAML and C# Edition to learn techniques, tools, and ideas to create successful, 5-star apps. Windows 8 App Projects - XAML and C# Edition shows you the nuts and bolts of the Windows 8 development ecosystem. Then, through a series of example driven chapters, you'll discover how to leverage the platform’s unique features. With each project, you'll be one step closer to building full-featured, responsive, and well designed apps that feel like they’re a part of the operating system. Windows 8 App Projects - XAML and C# Edition is a great book for developers that already know their way around the .net framework and want to leverage their existing knowledge into building apps for the new and exciting Windows RT platform and the great touch-first tablet and hybrid devices that accompany Windows 8 to market. Learn to build apps for Windows 8 in an example driven way Leverage existing skills onto the Windows 8 platform Get to know and use the new Modern UI style to make your apps stand out.
Keywords: Microsoft software; Microsoft .NET Framework; Software engineering; Microsoft and .NET.; Software Engineering/Programming and Operating Systems